Study on the effect of phenoxyethanol–citric acid pretreatment for the enzymatic hydrolysis of bamboo residues - Cheng, Yan; Zhao, Xiaoxue; Li, Ruolin; Liao, Jili; Huang, Caoxing (Frontiers in Bioengineering and Biotechnology, 2024)
This study investigated the biphasic phenoxyethanol-citric acid (PECA) pretreatment for bamboo residues (BR) and its corresponding effects on the enzymatic hydrolysis performance. It is found that increasing the concentration of citric acid in the pretreatment system from 2.5% to 15% greatly enhanced the delignification and xylan removal for BR. Consequently, the enzymatic hydrolysis yield of pretreated BR significantly enhanced, increasing from 12.4% to 58.2% and 28.0% to 72.4% when the citric acid was increased from 2.5% to 15.0% at 160 ℃ and 170 ℃, respectively.Characterization results from cellulose crystallinity, accessibility, and hydrophobicity of pretreated bamboo residues indicated that their changes possessed a beneficial performance on the enzymatic hydrolysis yield, which could result from the synergistic removing of lignin and xylan. Through Chrastil model analysis, it can be known that pretreatment at higher conditions resulted in the pretreated BR possessing weaker diffusion resistance for cellulase, which is attributed to its higher enzymatic hydrolysis yield.